Cyanospirobifluorene-based conjugated polyelectrolytes: Synthesis and tunable nonvolatile information storage performance. (15th January 2022) - Wang, Kexin; Wang, Xinzhu; El-Khouly, Mohamed E.; Che, Qiang; Zhao, Zhizheng; Zhang, Bin; Chen, Yu
Graphical abstract: Novel soluble conjugated polyelectrolytes with different content of the ionic functionalities are synthesized. These materials exhibit the tunable nonvolatile memory performance. Highlights: The soluble cyanospirobifluorene-based conjugated polyelectrolytes were successfully synthesized. These polymers exhibited very interesting filamentary nature upon being subjected to voltages. The as-fabricated electronic devices show tunable nonvolatile memory performance. Electrons dominate the conduct process in the as-fabticated memory devices. Abstract: Novel soluble cyanospirobifluorene-based conjugated polymers were synthesized by the Suzuki coupling copolymerization of 2′, 7′-dibromo-2, 7-bis(4′-cyanophenyl)-9, 9′-spirobifluorene (M1), 2, 7-bis(4, 4, 5, 5-tetramethyl-1, 3, 2-dioxaborolan-2-yl)-9, 9-dioctylfluorene (M2) and 2, 7-dibromo-9, 9-bis(6-bromohexyl) fluorene (M3). In an attempt to select the optimal ratio of the monomers, copolymers with different ratios of monomers were prepared via Suzuki-coupling reactions. The feed molar ratios between M1 and M3 were 1:0, 3:1, 1:1, 1:3, and 0:1 in PCSF, PCSFBF-1, PCSFBF-2, PCSFBF-3 and PFBF, respectively. The last four polymers were used to react with excessive amounts of N -methyl imidazole in the presence of acetonitrile to give polyelectrolytes PCSFF-1, PCSFF-2, PCSFF-3 and PFIF. Incorporation of the rigid cyanospirobifluorene moieties into the polymer structure could significantly improve the thermal stability of the resultant material. The as-fabricated Al/PCSF/ITO device exhibits a typical nonvolatile rewritable information storage performance, with a switch-on voltage of 1.95 V and a switch-off voltage of −3.67 V. Similarly, PCSFF-based devices also show similar information storage performance as that of PCSF-based device. The observed switch-on/off voltages are 1.77/-3.34 V for PCSFF-1; 1.57/-2.15 V for PCSFF-2; and 1.70/-2.39 V for PCSFF-3. The as-synthesized PFIF without cyanospirobifluorene unit only displays a nonvolatile WORM (write-once–read-many-times) type information storage performance, with a switch-on voltage of 1.95 V. Upon being subject to voltages, these polymers exhibited very interesting filamentary nature. This work shows a very promising strategy to tailor nonvolatile information storage performance of the polymer materials via local electrostatic fields resulted from the ionic functionalities in the resultant polymer.